SYNTHESIS OF SOME NOVEL PERYLENE DI IMIDES AND EVALUATION OF THEIR ANTI CANCER ACTIVITY - CN, Hemalatha; M, Vijey Aanandhi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The main objective of the study is to synthesis some novel perylene di imides and to evaluate for anti oxidant activity and anticancer activity. Methods: Antioxidant assay was carried on to study the reducing activity of the compounds. The cytotoxicity assay was studied to find the best potent compound among the synthesized compound by using the HCT-116, a colon cancer cell line. Synthesized substituted amine derivatives of perylene di imides. From the evaluation study Compound, A shows potent activity when compared with the standard drug 5-Fluorouracil. Results: The results of the total antioxidant capacity assay of perylene compounds are evaluated by the 1,1-diphenyl-2-picryl hydrazyl (DPPH) method and nitric oxide scavenging method. All the synthesized compounds are evaluated for their antioxidant power. From the results of DPPH and nitric oxide scavenging assay, Compound A, B, C and D showed potent activity when compared with the standard. For further evaluation of cell line studies, based upon the IC50 values, Compound A, B and C were taken for study. The molecular modeling data's are exactly correlated with the in vitro studies. We have used 5-Fluorouracil and PIPER as a standard for in vitro study and molecular modeling study respectively. Conclusions: From the results, Compound A will be efficient to inhibit telomerase enzyme and the Compound A will be effective for anti-cancer therapy.